Pelaksanaan Hak Pilih Masyarakat Baduy di Desa Kanekes Kabupaten Lebak Pada Pemilihan Umum 2019 - Ressy Puspita Sari; Yuslim Yuslim; Dian Bakti Setiawan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This research aims to find out how the implementation of voting rights and the challenges faced in the implementation of voting rights of the Baduy community in Kanekes Village, Lebak Regency in the 2019 general election. The research uses a juridical-empirical method with data collected through document study and interview by using purposive sampling and snowball technique which is done directly through a list of questions and conducted on a rolling basis. All data obtained from the research will be compiled and analyzed qualitatively which includes data reduction, data presentation, and conclusion drawing. This study concludes that the Inner Baduy community has stricter rules in carrying out customary law it results in a prohibition on the establishment of polling stations in the Inner Baduy area, in addition to the existence of the Lunang customary value or Milu Kanu Meunang which is believed by the Baduy community, namely following the winner, this is an attitude of accepting and obeying government rules regardless of whoever the candidate or party wins the electoral contestation, this makes some of the Baduy community, especially the Inner Baduy, do not use their voting rights.